PURIFIKASI DAN KARAKTERISASI MERKURI REDUKTASE Isolat Streptomyces spp. RIZOSFER RUMPUT TEKI DI DAERAH TERCEMAR MERKURI - , HANUM MUKTI RAHAYU; , Dr. Yekti Asih Purwestri, S.Si, M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Purification and characterization mercuric reductase four isolates Streptomyces (Streptomyces sp. AS1, Streptomyces sp. AS2, Streptomyces sp. AS6, and Streptomyces sp. BR28) have been investigated. Cell free extract was obtained by disrupting cells using sea sand at 4 Â°C and followed by centrifugation. Mercuric reductase was purified by ammonium sulfat precipitation, dialysis, and chromatography column (DEAE Sepharose anion column chromatography). Determination pH and temperature optimum of mercuric reductase activity based on the number of NADPH2 oxidized to NADP per mg protein per minute by using a spectrophotometer. Molecular weight mercuric reductase determined using SDS-PAGE. The result showed spesific activity of mercuric reductase Streptomyces sp. BR28 was the highest. The optimum pH and temperature cellfree extract enzyme mercuric reductase were 7,5 and 80 Â°C, respectively. The enzyme was purified to 431,87-fold with spesific activity 21918,95 U/mg protein. SDS PAGE showed that Streptomyces sp. BR 28 has mercuric reductase. It can be concluded that Streptomyces isolates have mercuric reductase and be potential as a bioremediation agent.